Adhesive Capsulitis Among Diabetic Patients Attending in a Tertiary Care Hospital in Dhaka, Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Adhesive capsulitis also termed as frozen shoulder is a condition characterized by painful and limited active and passive range of motions of the shoulder. It can adversely affect activities of daily living and consequently impair quality of life. The aim of the study was to estimate the prevalence of adhesive capsulitis among diabetic individuals and to study its relationship with age, gender, involved shoulder, body mass index (BMI) and glycaemic control.Method: A cross-sectional observational study was done in 290 patients attending outpatient department of BIRDEM hospital during the period from1st April 2023 to 30th September 2023. Convenient type of sampling technique was applied. Patients with shoulder pain and restricted active and passive shoulder joint movements were diagnosed as having adhesive capsulitis. Data were statistically analyzed.Results: Adhesive capsulitis was present in 54 (18.62%) of patients with diabetes. It was found that adhesive capsulitis was higher in increasing age, predominant in female 34(63.0%), more involve in left shoulder 27(50%). Statistically significant association was found with poor glycaemic status.Conclusion: Adhesive capsulitis is a common problem in diabetic patients. Its occurrence was found to be prevalent with poorly controlled glycaemic status.J Bangladesh Coll Phys Surg 2024; 42: 230-234